Performance Indices Based Optimal Tunning Criterion for Speed Control of DC Drives Using GA - Deepti Singh; Brijesh Singh; Nitin Singh (Institute of Advanced Engineering and Science, 2014)
This paper presents a framework to carry out a simulation to tune the speed controller gains for known input of DC drive system. The objective is to find the optimal controller gains (proportional and integral) in a closed loop system. Various performance indices have been considered as optimal criterion in this work. The optimal gain values have been obtained by conventional and Genetic Algorithm (GA) based optimization methods. The study has been conducted on a simulink model of three phase converter controlled direct current (DC) drive with current and speed control strategy. The results show that the GA based tunning provided better solutions as compared to conventional optimization methods based tunning.DOI: http://dx.doi.org/10.11591/ijpeds.v4i4.6334